A review on the genus Trapelus Cuvier, 1817 (Sauria: Agamidae) in the Iranian Plateau - Golnaz Eftekharzadeh; Nasrullah Rastegar-Pouyani; Eskandar Rastegar Pouyani (Iranian Journal of Animal Biosystematics, 2022)
The genus Trapelus Cuvier, 1817, belonging to the subfamily Agaminae, is described with 13 species. There are absolutely four species in Iran: T. agilis, T. ruderatus, T. sanguinolentus and T. persicus. Within the vast distribution range of Trapelus, current and past climate and vicariance events have significantly influenced their diversification patterns and distributions. Recently, the first and the most comprehensive assessment based on molecular genetic analyses within T. ruderatus in western Asia including Iran, Turkey, Syria, and Iraq, has shown that Iranian populations have slight divergence whereas are undoubtedly isolated from Turkey's population. Also, this study introduced the populations of southern Iraq as belonging to T. persicus. In this review, we have tried to have a complete examination and comparison based on all of the available relevant literature about the taxonomy, phylogeny, evolutionary history, and biogeography of the genus Trapelus in the Iranian plateau and neighboring regions, as well as we examined the controversial nomenclature changes and their reasons in some species and subspecies of this genus. We will also give a briefoverview of our unpublished dissertation on comparative morphology and dimorphism in the genus T. ruderatus. In the end, we present an identification key based on the latest changes in the classification and taxonomy of the genus.